The effect of financial performance, IOS, and firm size on cash holdings: the role of dividend policy as moderating variable - Woen Cliff Wibowo; Sugeng Wahyudi (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2019)
This study aims to determine and analyze the effect of financial performance (profitability, leverage, capital expenditure, liquid asset substitute), IOS, and company size on cash holding by using dividend policy as a moderating variable. The number of samples of this study was 108 observations of non-financial companies in the LQ 45 Index for the period of 2011-2016. The results of moderated regression analysis (MRA) shows that profitability has a positive effect on cash holding, while leverage, liquid asset substitute, IOS, and firm size have negative effect on cash holdings. The results of this study also show that dividend policy can be a moderating variable which weakens the positive effect of profitability on cash holding and strengthens the negative effect of capital expenditure, but the dividend policy is not able to moderate the influence of leverage on cash holding. As a result, the companies were able to make large dividend payouts to reduce the excessive amount of cash holding that managers often abused for their own benefits and increasingly prospering investors with a given dividend.